2009
DOI: 10.1080/00986280903425870
|View full text |Cite
|
Sign up to set email alerts
|

To Get Involved or Not: The Relation among Extracurricular Involvement, Satisfaction, and Academic Achievement

Abstract: This study examined the relation among extracurricular involvement in psychology-related activities, satisfaction, and academic achievement in graduating psychology majors. We surveyed 71 seniors (53 women and 18 men, M ag e = 24.84 years) about their involvement in psychology-related activities (e.g., Psi Chi, serving as a research assistant), satisfaction with experiences as a psychology major, and grade point average (GPA). Involvement was related to satisfaction and GPA, but satisfaction was not related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 13 publications
(31 reference statements)
3
29
1
1
Order By: Relevance
“…Furthermore, honor societies like Psi Chi encourage student engagement by providing frequent interactions between students and faculty, as well as leadership mentoring opportunities (Skinner and Belmont, 1993). Involvement in psychology-specific activities, including Psi Chi, has been shown to be positively correlated with student satisfaction with their major, as well as with grade point average (Strapp and Farr, 2010).…”
Section: Examples Of Student-based Learning Communitiesmentioning
confidence: 99%
“…Furthermore, honor societies like Psi Chi encourage student engagement by providing frequent interactions between students and faculty, as well as leadership mentoring opportunities (Skinner and Belmont, 1993). Involvement in psychology-specific activities, including Psi Chi, has been shown to be positively correlated with student satisfaction with their major, as well as with grade point average (Strapp and Farr, 2010).…”
Section: Examples Of Student-based Learning Communitiesmentioning
confidence: 99%
“…A landmark study conducted by Astin (1996) identified what components of college most influence cognitive and affective development-academic engagement, connection with faculty, and participation in student peer groups. Furthermore, Strapp and Farr (2010) documented a relationship between club participation and job market preparedness, indicating that student organizations are a viable resource for skill building. McCannon & Bennett (1996) identified rationales for student involvement, including the desire for experience, resume building, and meeting people with shared interests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, students who are involved in campus activities experience greater gains in cognitive and affective development, achieve greater academic success, report higher life satisfaction, and build more life skills. (Harper & Quaye, 2007;Krumrei-Mancuso, Newton, Kim, & Wilcox, 2013;Montelongo, 2002;Strapp & Farr, 2010). In general, students who are involved in campus activities experience greater gains in cognitive and affective development, achieve greater academic success, report higher life satisfaction, and build more life skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, serious qualitative and quantitative research has been carried out, and a positive connection between the level of academic achievement and the involvement of the student in extracurricular activities has been concluded (Bakoban & Aljarallah, 2015;Zacherman & Foubert, 2014;Strapp & Farr, 2010). The influence of extracurricular activities on the ability to find employment and professional adaptability (extracurricular short-and long-term effects on employability) is analyzed in Clark et al, 2015. A number of Russian and foreign publications discuss the role of extracurricular activities in the process of multi-cultural education, the development of the ability to intercultural interaction in future specialists, and tolerant perception of social and cultural differences (Cheng & Zhao, 2006;Musaev, 2014;Logvinova, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%